On Estimates for the Bessel Transform in the Space Lp,α(R+): R. Daher, M. El Hamma - Team, Support (Thai Journal of Mathematics, 2013)
In this paper, we prove the estimates for the Bessel transform in L _p,α(R_+) as applied to some classes of functions characterized by a generalized modulus of continuity.